2023
DOI: 10.1007/s00127-023-02430-2
|View full text |Cite
|
Sign up to set email alerts
|

Canadian news media coverage of suicide during the COVID-19 pandemic

Abstract: Purpose The COVID-19 pandemic led to concerns about increases in suicidal behaviour. Research indicates that certain types of media coverage of suicide may help reduce suicidality (the Papageno effect), while other types may increase suicidality (the Werther effect). This study aimed to examine the tone and content of Canadian news articles about suicide during the first year of the pandemic. Methods Articles about suicide from Canadian news sources were collected and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
0
1
Order By: Relevance
“…We found that, postimplementation, the national initiative was associated with substantial reductions in putatively harmful content and across-the-board increases in the proportion of articles with putatively protective content, a finding aligned with other recent Canadian research on media and suicide. [34][35][36] This finding differs somewhat from what we observed immediately after the release of the Mindset Guidelines and following the combined initiative onset. The release and dissemination of Mindset Guidelines coincided with some positive changes that appeared to persist over time (e.g., a greater proportion of articles presenting alternatives to suicide), but also negative changes that persisted for some years (e.g., a greater proportion of articles describing suicide methods in detail, presenting simplistic reasons for suicide).…”
Section: Discussioncontrasting
confidence: 99%
“…We found that, postimplementation, the national initiative was associated with substantial reductions in putatively harmful content and across-the-board increases in the proportion of articles with putatively protective content, a finding aligned with other recent Canadian research on media and suicide. [34][35][36] This finding differs somewhat from what we observed immediately after the release of the Mindset Guidelines and following the combined initiative onset. The release and dissemination of Mindset Guidelines coincided with some positive changes that appeared to persist over time (e.g., a greater proportion of articles presenting alternatives to suicide), but also negative changes that persisted for some years (e.g., a greater proportion of articles describing suicide methods in detail, presenting simplistic reasons for suicide).…”
Section: Discussioncontrasting
confidence: 99%